Study on compressive bearing capacity of concrete-filled square steel tube column reinforced by circular steel tube inside - Zhang, Yufen; Zhao, Junhai; Yuan, Weifeng (Journal of Civil Engineering and Management, 2013)
This paper concentrates on the compressive bearing capacity of one composite column of a Concrete-Filled Square Steel Tube (CFSST) reinforced by a circular steel tube inside. Some tests were conducted to consider the compression behaviour of the stub columns under axial compressive loading. Through an elastoplastic limit analysis based on Unified Strength Theory (UST), the ultimate load capacity of the CFSST columns reinforced by inner circular steel tube under axial compression has been derived, which has a good agreement with the experimental results in comparison with other empirical models. So this model is extended to predict the optimal design of the inner tube, namely, Di/ti and Di/B. In addition, another simple model is also proposed to testify the optimal section of this composite column. With the optimal circular steel tubes inside the CFSST column, the composite column can result in significant savings in column size, which ultimately can lead to significant economic savings and higher bearing capacity. The results show that it has a theoretical significance and application value to adopt circular steel tube to strengthen CFSST column. First published online: 24 Oct 2013